Jesus for farmers and fishers : Justice for all those marginalized by our food system - Nabhan, Gary Paul (Broadleaf Books, 2021)
Food producers in America are in the midst of one of the most severe farm crises of the last half-century. Yet we are largely unaware of the plight of those whose hands and hearts toil to sustain us. In Jesus for Farmers and Fishers, Gary Nabhan offers a fresh look at the parables of Jesus to bring us into a heart of compassion for those in the food economy hit by this crisis.